Exploring the Relevance of Advanced Mathematical Knowledge for Secondary-Level Instruction - Chhetri, Deb Bahadur; Khanal, Bishnu (Academic Journal of Mathematics Education, 2023)
The usefulness of advanced mathematics in teaching is referred to as its relevance for secondary-level mathematics instruction. This paper is based on research that explores teachers' views on the relevancy of advanced mathematics and their expectations from advanced mathematics courses for teacher preparation programs. Ten secondary-level mathematics teachers participated in this study. semi-structured interviews with open-ended questions and focus group discussions were utilised for data collection and thematic for data analysis. The finding indicates that advanced mathematics is relevant for developing mathematical proficiency, mathematical, and logical thinking, knowledge of mathematical context mathematical activities and increased problem-solving skills and professional competencies. Along with advanced mathematical knowledge, technological and research knowledge, and skills are expected from undergraduate teacher preparation courses. Therefore, it is suggested to incorporate the expected form of knowledge in the teacher preparation program.